Al-Muhtawâ al-Ma’rifi wa ats-Tsaqâfi fî Kitâb Ta’lîm Al-Lughah Al-‘Arabiyyah li Wizârah Asy-Syuûn Ad-Dîniyyah ‘âm 2020 - Komaludin, Jajang; Mufidah, Nuril; Munjiah, Ma'rifatul (Postgraduate of IAIN Metro Lampung Indonesia, 2023)
This research aims to reveal the appropriateness of the cognitive and cultural content of the Arabic language teaching book (third intermediate grade) of the Ministry of Religious Affairs in 2020 in light of Al-Khuuli's standards. The method used is the descriptive analytical approach with the qualitative approach through the content analysis method. To analyze the data, the researcher used the Mils-Hubermann model, which consists of four steps: data collection is done through documents, their classification, presentation and conclusion. The knowledge and cultural content of the Arabic language teachingbook (third intermediate grade) of the Ministry of Religious Affairs in 2020 in general is commensurate with the standards of Al-Khouli, in order to adapt the content to the age and level of knowledge of the learners, and to take into account their values with the diversity of the content, and to include the desired culture, and the realism of the content with its health is useful for learners and satisfies their needs, but some shortcomings were found with regard to aspects of values, culture and content validity.